Citra Perempuan dalam Novel Sujud Nisa di Kaki Tahajjud Subuh Karya Kartini Nainggolan: Tinjauan Kritik Sastra Feminis - Wiwik Rahayu; Sri Suciati; Muhajir Muhajir (Universitas PGRI Semarang, 2023)
This study aims to describe the image of women in the novel Sujud Nisa Di Kaki Tahajjud Subuh by Kartini Nainggolan and to describe the form of women's resistance in the novel Sujud Nisa Di Kaki Tahajjud Subuh by Kartini Nainggolan. The method used in this study is a qualitative method to describe the image of women and the forms of women's resistance contained in the novel. The data collection techniques for this research are library research techniques, note-taking techniques, and data cards. From the results of the analysis carried out, it is obtained that the image of women in the novel is in the form of a self-image that is realized physically and psychologically as well as the social image of women in the family and social image in society. Physical self-image as an adult woman who has experienced pregnancy, childbirth, breastfeeding, and caring for her child. Psychological self-image as a psychological woman who thinks, feels, and has aspirations. While the social image in the family is as a member of the family, as a child, a wife, and a mother. The social image in society is women who have influence in society and women who need other humans to achieve their perfection. In addition, data on the forms of women's resistance were also found in the form of being independent women, refusing to marry young, and refusing arranged marriages.Keywords: image of women, women's resistance, literary works, novels, feminist literary criticismAbstrakÂ Penelitian ini betujuan mendeskripsikan citra perempuan dalam novel Sujud Nisa di Kaki Tahajjud Subuh karya Kartini Nainggolan. Metode yang digunakan dalam penelitian ini adalah metode kualitatif untuk mendeskripsikan citra perempuan yang terdapat dalam novel. Teknik pengumpulan data penelitian ini adalah teknik studi pustaka, teknik simak catat, dan kartu data. Dari hasil analisis yang dilakukan diperoleh citra perempuan dalam novel berupa citra diri yang diwujudkan secara fisik dan psikis serta citra sosial perempuan dalam keluarga dan citra sosial dalam masyarakat. Citra diri secara fisik sebagai perempuan dewasa yang telah mengalami kehamilan, melahirkan, menyusui, dan merawat anaknya. Citra diri secara psikis sebagai perempuan pikologi yang berpikir, berperasaan, dan beraspirasi. Citra sosial dalam keluarga yaitu sebagai salah satu anggota keluarga, sebagai anak, seorang istri, dan seorang ibu. Citra sosial dalam masyarakat yaitu perempuan yang memiliki pengaruh dalam masyarakat dan perempuan yang memerlukan manusia lain untuk mencapai kesempurnaan dirinya.Kata kunci: citra perempuan, deskriminasi gender, karya sastra, novel, kritik sastra feminis